Design, fabrication, evaluation of low-speed UAV wing flap actuated with shape memory alloy - Seow, Aik Khiam (2009)
The novel properties of shape memory alloys (SMA) are very attractive for providing new solutions to challenging problems in aerospace engineering. Although SMA possess very high kinetic output and instantaneous actuation upon heating, owing to their slow cooling rate, difficulties have been encountered in using them as actuation mechanisms for some aerospace applications requiring repeated actuations under relatively high frequency. The project is a feasibility study to control a wing flap using SMA. Attention has been paid to conceptual design of actuation mechanisms, controllability of the actuation, and the response rate of SMA actuation. It is known that the cooling rate of SMA depends on several parameters including the materials characteristics, the geometric factor and the environmental condition. By optimizing the first two factors and taking into account the third and fourth parameters, it is possible to optimize the cooling speed of SMA thus increasing the actuation frequency within a certain range allowed by the design. The project will progress through four phases; the first phase is to understand the principles behind the shape memory effect, and this is done through extensive heat treatments, thermo-mechanical trainings and measurement. It is then followed by design, fabrication and actuation tests for two concepts, namely the shim-based version and hinge-based version. Flexible skins, a key requirement to smooth camber change, are also explored and experimented. A mechanism that will engage and disengage the SMA wires during operation is also studied. Finally, the controllability of actuation is studied.